2021
DOI: 10.1002/jev2.12157
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from the periodontal pathogen Filifactor alocis induce systemic bone loss through Toll‐like receptor 2

Abstract: Periodontitis is an inflammatory disease induced by local infection in toothsupporting tissue. Periodontitis is associated with systemic bone diseases, but little is known about the mechanism of the causal effect of periodontitis on systemic bone resorption. Bacteria-derived extracellular vesicles (EVs) act as natural carriers of virulence factors that are responsible for systemic inflammation. In this study, we investigated the role of EVs derived from Filifactor alocis, a Gram-positive, anaerobic periodontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 74 publications
(91 reference statements)
3
33
0
Order By: Relevance
“…TLR2 signalling plays an important role in T. forsythia -mediated alveolar bone loss and activation of osteoclasts 20 . The osteoclastogenic activity of Pg EVs and Tf EVs was reduced by lipoprotein lipase treatment, suggesting that lipoproteins are active molecules, as shown in our previous study 15 . Jain et al reported that P. gingivalis induced inflammation via TLR2 signalling, which was attenuated by lipoprotein lipase treatment 21 .…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…TLR2 signalling plays an important role in T. forsythia -mediated alveolar bone loss and activation of osteoclasts 20 . The osteoclastogenic activity of Pg EVs and Tf EVs was reduced by lipoprotein lipase treatment, suggesting that lipoproteins are active molecules, as shown in our previous study 15 . Jain et al reported that P. gingivalis induced inflammation via TLR2 signalling, which was attenuated by lipoprotein lipase treatment 21 .…”
Section: Discussionsupporting
confidence: 83%
“…Local infection of periodontal pathogens can cause osteoclast differentiation and bone resorption 17 . Recently, we determined that EVs from the Gram-positive periodontal pathogen F. alocis efficiently induce osteoclast differentiation and activation 15 . We used Fa EVs as a positive control to induce osteoclast differentiation in further experiments in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations